Differences in thermostable actin profile of goat meat as observed in two-dimensional gel electrophoresis (2DE) - Zainal Abidin, Siti Aimi Sarah; Karsani, Saiful Anuar; Ismail, Amin; Khairil Mokhtar, Nur Fadhilah; Sazili, Awis Qurni (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
Different heat treatments, (1) chilled, 4°C (2) boiled at 100°C for 30 min and (3) autoclaved at 121°C at 15 psi for 20 min were employed on goat meat to mimic domestic and industrial cooking. The effects on intensity of actin proteins was observed using two-dimensional gel electrophoresis where significant differences (p>0.05) were observed in the spot intensity between chilled and boiled samples, similarly in chilled and autoclaved samples. However, no significant difference was observed between boiled and autoclaved samples. The slight changes observed in the cooking of meat confirmed that actin protein is susceptible to denaturation cause by heat. MALDI-TOF/TOF analysis revealed the peptide-mass fingerprint between positions 21 - 374 that not affected by heat treatment. Peptides from this position merit the candidature of actin as putative thermostable marker for detecting goat meat (chevon) in food product.